Digitizing Scoring Systems With Extended Online Feedback: A Novel Approach to Interactive Teaching and Learning in Formative OSCE - Wang, Chia-Chen; Wang, Yu-Chin Lily; Hsu, Yu-Han; Lee, Haw-Chyuan; Kang, Yu-Chan; Monrouxe, Lynn Valerie; Chien, Shao-Ju; Chen, Te-Chuan (Frontiers in Medicine, 2022)
OBJECTIVES Objective structured clinical examinations (OSCEs) are common for formative assessment. We developed an Online Smart Communicative Education System and aimed to explore the factors that affect the perceptions of teachers and students for teaching and learning. METHODS AND ANALYSIS A two-year cross-sectional cohort study was undertaken. The program includes three parts. Part I Pre-OSCE: an online flipped class in preparation for task-related knowledge and skills. Part II OSCE-day: 10 tasks in one track formative OSCE. Part III Post-OSCE: extended online feedback for participants with further questions after the exam and raters with more feedback after reviewing their performance online. Principal component analysis with varimax rotation was performed to analyze the perceptions of students and teachers to the Online System by means of questionnaires. RESULTS Seventy-six pharmacy students (male 32.9%) took the exam and 24 raters (male 25%) participated in the scoring during the OSCEs. The mean G coefficient was 0.88. Seventy-six questionnaires from the students were obtained for the analysis. Results explained the cumulative variance of 73.9% for component 1) “Effects of extended online feedback”: 40.0% and 2) “Facilitation of learning”: 33.9%. Thirty-nine questionnaires from the raters who experienced the Online System were obtained for the analysis (male 23.1%). Results explained cumulative variance of 77.3% for component 1) “Effects of extended online feedback”: 36.6%, 2) “Facilitation of scoring and feedback”: 24.5%, and 3) “Feasibility of online platform”: 16.2% respectively. CONCLUSIONS We demonstrated good reliability for digitizing scoring system with educational support to facilitate teaching. “Effects of extended online feedback” was the major aspect for explaining the variance from students’ and raters’ perceptions by factor analysis. In comparison with traditional formative OSCEs, extended online feedback is a novel approach, which extends the process of learning and teaching among the learners and raters and overcomes the barriers of time limitation and distance.